Advanced parental age: Is it contributing to an increased incidence of non-syndromic craniosynostosis? A review of case-control studies - Kenzy Abdelhamid; Rea Konci; Hassan ElHawary; Andrew Gorgy; Lee Smith (Journal of Oral Biology and Craniofacial Research)
Background: Craniosynostosis (CS) is a congenital birth defect characterized by the premature fusion of one or several calvarial suture(s). CS could lead to serious complications, such as intracranial hypertension and neurodevelopmental impairment. There is an increasing trend in the prevalence of CS – 75% of which are of non-syndromic type (NSCS). In parallel, there is a steady rise in the average maternal age. The goal of this paper was to review the literature to clearly identify any associations between parental age and NSCS. This review was performed and reported in compliance with PRISMA guidelines. Methods: The PUBMED and EMBASE databases were systematically searched, and all studies that observed the relationship between maternal and/or paternal age on NSCS were included. The articles were then assessed for methodological quality using the Newcastle–Ottawa Scale (NOS). The effect of advanced maternal and/or paternal age on the incidence of NSCS was identified by the prevalence ratios reported at a confidence interval of 95%. Results: Six retrospective case-control studies, reporting on a total of 3267 cases of NSCS were included in this review. While there were some inconsistencies in the findings of the different studies, the majority reported a positive correlation between advanced maternal and/or paternal age and an increased incidence of NSCS. Conclusion: This review identified an association between advanced parental age and an increased incidence of NSCS.